RELATIVE AGE EFFECT AMONG OLYMPIAN GYMNASTS - Delaš Kalinski Sunčica; Petra Mandić Jelaska; Almir Atiković (University of Ljubljana Press (Založba Univerze v Ljubljani), 2018)
Relative age effect (RAE) is a worldwide phenomenon described as consequences of age variations between individuals competing in the same cohort. RAE is based on systems that use January 1 as a cut-off date, probably used to attempt to minimize developmental differences between ages and to ensure a more equitable competition. Previously, in artistic gymnastics, a majority of studies on RAE was conducted in gymnasts of national levels. This study analysed RAE both among and between elite female (NF=1268) and male gymnasts (NM=1186) who participated at all Olympic Games held from 1964 to 2016. By using χ2 test, significant difference were found: 1) within frequencies of total sample of male gymnasts born in a certain month (p<0.001); 2) within frequencies of groups of male gymnasts apparatus finalists born in a certain month (p<0.005); 3) within frequencies of groups of male apparatus finalists born in a certain quarter of the year (p<0.005); 4) within frequencies of groups of male apparatus finalists born in a certain half of the year (p<0.005). As far as female gymnasts are concerned, significant differences have not been found within frequencies of any female group born in a certain month, quarter or halves of the year. Regarding differences between genders, no significant differences have been obtained between frequencies of male and female gymnasts born in certain month, quarter and halves of the year. Despite certain differences among and between genders, the general conclusion was that RAE is not present in elite gymnasts of both genders.